Empowering Working Adults Through Digital Literacy: A Case Study of Community-Based Education in Rural Indonesia - Arbain, Arbain; Sujarwo, Sujarwo (Papanda Publisher, 2025)
The proliferation of internet users in Indonesia has not been matched by adequate digital literacy competencies, resulting in misinformation spread, cyberbullying, and inappropriate content consumption, particularly among populations with limited formal education. This qualitative evaluation research was conducted at PKBM Napal Jaya from August to October 2024, employing a comprehensive framework encompassing contextual background, input resources, implementation processes, goal achievement, and program impacts. Data were collected through observations, semi-structured interviews with four key informant groups (PKBM head, tutors, administrative staff, and learners), and document analysis. Miles and Huberman's interactive model was used for data analysis, with source triangulation ensuring trustworthiness. The program demonstrated systematic planning through participatory needs assessment, adequate infrastructure including computers and WiFi, qualified bachelor-degree tutors, and effective implementation using constructivist pedagogical approaches. Learners developed competencies in internet searching, hypertextual navigation, content evaluation, and knowledge assembly, transforming from recreational technology users to functionally literate digital citizens. Findings validate that community learning centers can successfully bridge digital divides through flexible, contextualized programming that accommodates working adults, providing a replicable model for non-formal education settings and contributing actionable guidance for practitioners addressing digital literacy gaps in developing country contexts.